Impact of Structure Modification on Texture of a Soymilk and Cow's Milk Gel Assessed Using the Napping Procedure. Issue 3 (11th March 2013) - Grygorczyk, A.; Lesschaeve, I.; Corredig, M.; Duizer, L.
Abstract It was hypothesized that with careful control of the structure of a mixed protein matrix, it is possible to obtain different textures without changing ingredients or their concentrations. A model system containing soymilk, cow's milk and cream was used. To modify the texture of the final matrix, the mode of protein gelation and the order of homogenization of the cream (with soymilk or skim milk alone or with both mixed together) were investigated. Using a partial Napping and ultra‐flash profiling procedure, it was demonstrated that as long as milk was homogenized with cream, the mixed protein gels had higher thickness and mouthcoating compared with gels made from unhomogenized samples or samples made by homogenizing the cream with soymilk. It was found that aggregation of milk proteins before soy proteins resulted in more prominent fat‐related attributes such as slipperiness and fattiness compared with simultaneous aggregation of casein and soy proteins. Practical Applications Recently, there has been a growing interest in mixed protein gels; however, little information exists about their sensory properties. Such gels have the potential to be a novel category of healthy high‐protein products exhibiting consumer‐acceptable sensory properties. However, more work is needed to improve understanding of how to generate such products and to understand the processes that impact their sensory properties. The aim of the present study was to examine the sensory texture changes induced when the organization of components is modified within a mixed soymilk–dairy milk gel without changing ingredients or their concentrations. The present study also contributes to the understanding of texture perception as it demonstrates a clear link between texture perception and structure modification in a protein gel. Mixed protein systems present an attractive opportunity for the study of texture–structure relationships as they allow the development of a range of structures without modifying the system's composition.